Friend or Foe? The Ambiguous Role of Innate Lymphoid Cells in Cancer Development. Issue 1 (January 2017) - Mattner, Jochen; Wirtz, Stefan
Abstract : The development of immunotherapies represents a major advance towards the effective eradication of malignant tumors. So far, therapeutic approaches have largely focused on T lymphocytes, but the innate arm of the immune system might be similarly important. Innate lymphoid cells (ILCs) are rapidly-responding cells that are functionally analogous to diverse T cell subsets. In recent years these cells have attracted enormous attention owing to their pleiotropic effects in early host defense to infection and organ pathologies. ILCs might also represent promising targets in the context of cancer therapy because they are an innate immune cell population endowed with potent immunomodulatory properties. In this review we discuss the impact of the three ILC subsets and the signature cytokines they release on cancer development and tumor growth. Trends: ILCs are categorized into three major subpopulations (ILC1s, ILC2s, ILC3s) that have key and non-redundant functions during infections as well as in the pathogenesis of inflammatory and allergic diseases. Recent evidence suggests that ILC subsets may have important roles both in tumor immunosurveillance and cancer promotion. ILC1s include conventional NK and lin − CD127 + cells that characteristically express IFN-γ and the transcription factor T-bet. They most likely inhibit malignant transformation and tumor growth. ILC2s abundantly secrete the type 2 cytokines IL-5 and IL-13, and are strongly implicated with a microenvironment promoting tumor growth and blocking antitumor immunity. ILC3s display dependency on RORγt and secrete IL-17 and IL-22. While in the case of inflammation-driven cancers there is evidence for a tumor-promoting role of ILC3, other studies have indicated direct antitumor functions.